Co(acac)2-Catalyzed Allylic and Benzylic Oxidation by tert-Butyl Hydroperoxide - Han, Xiaoqiang; Zhou, Ziyuan; Wan, Chuan; Xiao, Yumei; Qin, Zhaohai (Synthesis, 2013)
Various allylic and benzylic substrates were oxidized to the corresponding enones, arenealdehydes and aryl ketones in good yields with tert-butyl hydroperoxide in the presence of catalytic amounts of Co(acac)2 under mild conditions. The reactivity, selectivity, and scope of the reaction were investigated.
Keywords: Co(acac)2; allylic and benzylic oxidation; tert-butyl hydroperoxide; enones; benzaldehydes; ketones